Low‐Temperature Sintering of HfC/SiC Nanocomposites Using HfSi2‐C Additives. Issue 8 (14th May 2016) - Feng, Lun; Lee, Sea‐Hoon; Yin, Jie
Abstract : HfC/SiC nanocomposites were fabricated via the reactive spark plasma sintering (R‐SPS) of a nano‐HfC powder and HfSi2 ‐C sintering additives. The densification temperature decreased to 1750°C as the additive content increased. XRD analysis indicated the formation of pure HfC–(19.3–33.8 vol%) SiC within the sintered composites without residual silicide or oxide phases or secondary nonoxide phases. Ultrafine and homogeneously distributed HfC (470 nm) and SiC (300 nm) grains were obtained in the dense composites using nano‐HfC powder through the high‐energy ball‐milling of the raw powders and R‐SPS. Grain growth was further suppressed by the low‐temperature sintering using R‐SPS. No amorphous phase was identified at the grain boundary. The maximum Vickers hardness, Young's modulus, and fracture toughness values of the HfC/SiC nanocomposites were 22 GPa, 292 GPa, and 2.44 MPa·m 1/2, respectively.